This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
According to me the property cannot be applicable in case of these terms.According to pythagorean theorem,a^2 + b^2 = c^2 .
so, c = sqrt{a^2 + b^2}.
a = sqrt{c^2 - b^2}
b = sqrt{c^2 - a^2}
Subsituting these values in your equation a*b=c doesn't give equilibrium answer.